Dual-Mode Wound Rotor Synchronous Machine for Variable Speed Applications - Muhammad Ayub; Shahid Atiq; Qasim Ali; Asif Hussain; Byung-Il Kwon (IEEE Access, 2020)
This paper presents a novel dual-mode wound rotor synchronous machine (DWRSM) for variable speed applications. The proposed machine combines the advantages of both the conventional wound rotor synchronous machine (CWRSM) and the brushless wound rotor synchronous machine (BWRSM). Unlike the existing BWRSM, through the dual-mode operation of the proposed machine, constant torque is achieved in the constant torque region by operating the machine in mode-I, i.e., as a CWRSM, and constant power is achieved in the field weakening region by operating the machine in mode-II, i.e., as a BWRSM. The mode change is performed through an additional thyristor drive circuit. The airgap magnetomotive force (MMF) in both modes is derived analytically. To verify this principle, finite element analysis (FEA) and an experiment on a 1- horsepower prototype machine was performed, and key influential factors were verified. The transients in the stator currents and torque during the mode change was analyzed. The test results validated the correctness of the theory and the FEA results.